Branding Brand Image Strategy Study Through Digital Marketing Overview on MSMEs: Sanggabuana Coffee (KoSa) in Mekarbuana Village, Karawang - Dini Yani; Muhammad Yusuf; Ery Rosmawati; Zenita Apriani (Pusat Riset dan Inovasi Nasional, 2022)
Karawang Regency which is famous for its Industrial City turns out to have a lot of natural potentials that are not known by the wider community, even the native people of Karawang. One of the villages in South Karawang actually has so much natural potential that is located at the foot of Mount Sanggabuana. To support the income level of the community. One of them is through the introduction ofdigital marketing, where one of the biggest obstacles at this time is that digital promotion has not been carried out properly and correctly by the community so it is necessary to socialize the introduction of digital promotion.SMEs engaged in the production of Sanggabuana Coffee are digitized so that they can help SMEs to improve product quality and help SMEs understand the importance of digital marketing so that later they can reach a wider market. It is not surprising that the digitization program for MSMEs in Mekarbuana Village, Kec. Tegalwaru Regency. Karawang received a good positive response from the local community because it really helped the community, especially MSME actors. It is hoped that MSME actors can understand digital marketing so that later the marketing reach will not only be limited to Mekarbuana village but will extend outside the region in order to boost the economy.